Safety Instructions through AI: A Case Study of Unforgettable Supporters Display in Sports Stadiums - Tarrence Karmelia Kontessa (Jurnal Ilmu Multidisiplin, 2026)
Clear information about evacuation procedures in case of emergency will make spectators feel safe and comfortable during the event. However, in reality, such safety features are still rarely found in sports events in stadiums, especially in Indonesia “Unforgotten Supporters" is a concrete example of a risk communication practice presented through the application of artificial intelligence (AI) based safety instructions. This study aims to analyze the risk communication strategy in "Unforgotten Supporters", which is the result of collaboration between Kompas Daily and Dentsu Creative Indonesia, two different business entities that build cooperation because they both feel responsible for participating in educating the public through an interesting, creative and effective safety instruction display intended for spectators in stadiums, where safety risks are quite high. The research was conducted using a descriptive qualitative method. The analysis involves the risk communication strategy model according to (Sandman, 1993), and five important stages in the Diffusion of Innovation theory proposed by (Rogers, 2003), namely the knowledge, persuasion, decision, implementation and confirmation stages. The results show that “Unforgotten Supporters” uses a “precautionary advocacy” communication strategy where this strategy can prevent mass panic or overreaction from the public to a risk that is not yet fully understood. The AI-based safety instruction "Unforgotten Supporters" is an innovative step to increase the effectiveness of risk communication. However, this effort still needs to be continued because the confirmation stage according to Everett Rogers’ Diffusion of Innovation concept has not yet been achieved.